Scrutinizing The Epistemology of Islamic Economics: A Historical Analysis - Nurizal Ismail (TSAQAFAH, 2016)
The first International Conference on Islamic Economics was held in Makkah, in 1976. Economists, jurists and scholars met together to discuss issues of Muslim ummah. However, there was many books written related to Islamic economics in the history of Islamic civilization, especially in the period of Abbasid caliphate. The fact, development of knowledge in Islamic medieval had established the epistemology of Islamic economics itself. Moreover, the epistemology is a study of the theory of knowledge, the source of knowledge, the application of knowledge and limitation of knowledge. Therefore, this paper aims to explore the contribution of earlier Muslim thinkers to the source of Islamic economics and to identify the epistemology of Islamic economics as proposed by the Muslim thinkers in medieval period. As a result, this paper will propose the epistemology of Islamic economics by integrating Islamic heritage and modern economics that is not conflict with Islamic principles and values. To achieve its objectives; this study employs qualitative research by applying content and descriptive analysis. The finding of this study is that the earlier Muslim thinkers have contributed to the construction of epistemology in Islamic economics. Then, to construct the genuine of Islamic economics, tawhid must be put as a core of Islamic economic epistemology that directs the sources of knowledge which are rooted firstly from revealed and then rational knowledge by using appropriate methods.